SITI RAYATI: A Portrayal of an Indo-woman in the Dutch Colonial Era - Irfan Furqonnudin (Universitas Pendidikan Indonesia (UPI), 2014)
This study aims to investigate the descriptions of an Indo character in Moh. Sanoesi’s Siti Rayati and what alternative meanings can be found from the descriptions. Indo character was chosen because it is interesting to study, considering hybrid is the results of borderline engagements of cultural differences (Bhabha, 1994). To answer the questions, the data were gathered through textual analysis with close-reading approach. It was revealed that the Indo character is described in the sense of being superior, humble, in between and well-exposed by Dutch culture. From the categories, it may be inferred that there could have been an attempt by the writer to change the perception towards Indo-people’s stereotypes at that time.Keywords: Indo-People, Hybrid, Alternate-Meaning, Dutch Culture, Sundanese Society, Indo-People’s Stereotype